(untitled) (Лучшие интеллектуальные исследования, 2025)
Abstract: The goal is to study the technique of passing the ball from the top with two hands for 12-13-year-old volleyball players and to develop it rapidly with the help of selected action games. At the initial stage of training in sports technique, the issues of using mobile games were conducted on the example of young volleyball players. In the study, special exercises and action games aimed at forming the technique of receiving and passing the ball with two hands from above in 12-13-year-old volleyball players engaged in the initial training stage were selected based on the research.